A Comparative Study on Two Different Methods for Calculating Gravity Effect of an Uneven Layer: Application to Computation of Bouguer Gravity Anomaly in the East Vietnam Sea and Adjacent Areas - Pham Thanh, Luan (VNU Journal of Science: Mathematics - Physics, 2020)
Calculation of gravity anomaly caused by an uneven layer is essential for quantitative interpretation. By comparing calculated anomalies with observed anomalies, we may infer some parameters of subsurface structures. There are many different methods for computing gravity effect of an uneven layer. This paper presents a comparative study of two different forward methods such as the space domain method and the frequency domain method. The performance of each method was evaluated on two synthetic models. Finally, the more effective method was applied to calculate Bouguer gravity anomaly in the East Vietnam Sea and adjacent areas using the latest available dataset from the TOPEX mission.